2020
DOI: 10.3892/or.2020.7759
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑218 inhibits tumor angiogenesis of human renal cell carcinoma by targeting GAB2

Abstract: Renal cell carcinoma (RCC) is one of the most common malignant cancers in the adult urinary system worldwide. Tumor angiogenesis is a critical process during cancer progression, as it modulates carcinogenesis and metastasis. In recent years, microRNA-218 (miR-218) has been confirmed to play a crucial role in tumor suppression. However, the role of miR-218 in RCC angiogenesis remains unclear. In the present study, it was found that the expression of miR-218 was decreased in RCC tumor tissues and cell lines as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As the main pathological type of RCC, KIRC accounts for more than 80% of RCC ( Alsaab et al, 2018 ). Advanced patients with KIRC are not sensitive to radiotherapy and chemotherapy, and miss the opportunity of surgery because of metastasis ( Mu et al, 2020 ). Targeted therapy can benefit some patients, however, many advanced patients are ineffective to the existing targeted drug ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the main pathological type of RCC, KIRC accounts for more than 80% of RCC ( Alsaab et al, 2018 ). Advanced patients with KIRC are not sensitive to radiotherapy and chemotherapy, and miss the opportunity of surgery because of metastasis ( Mu et al, 2020 ). Targeted therapy can benefit some patients, however, many advanced patients are ineffective to the existing targeted drug ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, GAB2 was identified as a direct target of miR-218-5p, which is consisted with a previous report ( 36 ). It is well reported that miR-218 inhibited the tumor angiogenesis in human cancer via regulating the GAB2/PI3K/AKT signaling pathway in various cancer types ( 36 , 56 ). Thus, it was speculated that Sevo may have protective effects on HIRI via modulating the GAB2/AKT/mTOR signaling pathway by increasing miR-218-5p expression.…”
Section: Discussionmentioning
confidence: 99%
“…Such as, BATF is found to interact with JUNB to form heterodimer and then forms a complex with IRF4 in immune cells. After binding the AICE sequence (5'-TGAnTCA/GAAA-3'), an speci c regulatory factor formed and mediated cooperative gene activation [9][10]. The mechanisms of BATF regulation are diverse.…”
Section: Discussionmentioning
confidence: 99%